Indications of school culture in southeast Goiano: practices, standards and methods - Maria Almeida Barros, Aparecida; Rodrigues Luiz Peixoto, Patricia; Aparecida Caixeta, Sílvia (Seven Editora, 2023)
O study developed The leave gives question: which practices, standards and methods would be representatives of the institutionalized school culture in schools in southeastern Goiás, in the first a half of century XX? THE presence in practices, standards and methods investigated in three institutions schoolchildren, whose sample contemplated two schools confessional and one school agricultural federal, per quite gives Query The sources From collections schoolchildren, sought aspects distinct gives culture school internal. At the route methodological, dedicated The to locate you documents, characterize the sources by affinity and similarity, in order to obtain the variables that corroborate in the interpretation of traces of school culture marks in institutions, focusing on practices, norms and methods inscribed in official documents, referenced in authors and works from the history of school institutions. In the results we show The existence in practices, standards and methods, watching similarities and singularities, so much in the format and in the pedagogical didactic organization of these institutions, among the which stand out: you ends and goals educational, The emphasis at the disciplining gives conduct internal (regulations, norms, teaching programs, timetables, calendars); the interfaces of school with the society place and regional; the prescription of ducts and routines; O cult in internal symbols and rituals; the manifestations of obedience, discipline, and transgression; you levels in status and the representative distinctions gives schooled education DOI: 10.56238/pacfdnsv1-127